Cabin fever : surviving lockdown in the coronavirus pandemic - Crawford, Paul, 1963-; Crawford, Jamie Orion (SocietyNow., 2021)
This fascinating and timely book examines the distressing psychological syndrome of 'cabin fever' in the wake of the coronavirus pandemic and the greatest confinement of people to their homes in history, offering antidotes for it. Exploring the definitions and social and cultural history of cabin fever, a condition provoked by prolonged isolation, the book will be of interest to anyone concerned about the impact of current or any future pandemic lockdowns, prison life, remote living, or even travelling to Mars.